Breast Cancer and Meningioma Risk: A Mendelian Randomization Study - Jian‐Wei Huang; Yi‐Fei Wang; Ying‐Qing Hu; Hai‐Yong He; Shuang‐Qi Gao; Ying Guo (Brain and Behavior)
ABSTRACT Background The exact nature of the link between breast cancer and meningiomas is unknown, although observational studies have shown a correlation between the two. Using a two‐sample Mendelian randomization (MR) strategy, we aimed to investigate the effect of breast cancer on meningiomas. Methods Three sets of genetic instruments were utilized in this study based on publicly available genetic summary data. For breast cancer, we selected 62 strongly associated SNPs; separate datasets were curated for HER2‐positive and HER2‐negative subtypes. MR analyses included outlier testing, MR‐Egger regression, MR‐PRESSO, weighted median, and inverse variance weighted approaches. Results The inverse variance weighted analysis demonstrated significant evidence for breast cancer's effect on meningioma risk (OR = 1.213, 95% CI = 1.054–1.396, p = 0.007), supported by MR‐Egger (OR = 1.456, 95% CI = 1.066–1.988, p = 0.021) though not by the weighted median method (OR = 1.095, 95% CI = 0.914–1.311, p = 0.326). Inverse variance weighting specifically revealed a significant association between HER2‐positive breast cancer and meningioma incidence (OR = 1.203, 95% CI = 1.048–1.381, p = 0.009). Furthermore, breast cancer risk was associated with an increased incidence of malignant meningiomas (OR = 1.64, 95% CI = 1.12–2.40, p = 0.011). Conclusions This represents the first MR study investigating the causal relationship between breast cancer and meningiomas. Our findings support the hypothesis that breast cancer may increase meningioma risk.